Development of rice paper by using geminated Homnin brown rice flour - Chamchan, Rungrat; Chupeerach, Chaowanee; On-Nom, Nattira (Progress in Applied Science and Technology, 2017)
Health food is now being promoted among consumers due to its benefits such as reducing risk of non-communicable diseases. Germinated Homnin brown rice flour (GHNF) contains various health-promoting components such as dietary fiber, phytic acid, vitamins, gamma-aminobutyric acid (GABA), gamma-oryzanol and anthocyanin. Therefore, the objective of this study was to develop rice papers by using GHNF. Then, the effect of the ratio of GHNF:tapioca flour at 3 levels (45:55, 52:48 and 58:42) on the physical and chemical properties was determined, using rice papers made from rice flour as a reference. Moreover, sensory evaluation was conducted by 9-point hedonic scale. The results showed that water activity of all GHNF papers were in the range of 0.52-0.53. The tensile strength, cutting force and brittleness of 58% GHNF paper were not significantly different from the control (p≥0.05). The lightness (L*) were decreased while the redness (a*) was increased. However, the yellowness (b*) of all formulas were similar. The sensory evaluation indicated that the overall liking score of 58% GHNF paper obtained the highest score at 7.5 (like moderately to like very much). The chemical analysis found that the developed product had higher antioxidant activity and GABA content than control formula. Moreover, the GHNF rice papers showed medium glycemic index (GI). Therefore, this product was suitable for people who were health-exercising or the NCDs patients. Moreover, this can be an alternative option for adding value to the product and Thai rice.